Islam In Everyday Culture And “Wandering Mullahs” In Kazakhstan in the 1950s–1960s - Atanakova, Karlygash; Mazhitova, Zhanna; Yermagambetova, Kuralay (Journal of Ecohumanism, 2024)
This article explores the role of Islam in the daily culture of the Muslim communities in Soviet Kazakhstan during the 1950s and 1960s. Drawing from a diverse range of materials, including memos, reports, secret communications of party officials, and accounts from commissioners of the Council for Religious Cults, the research sheds light on various facets of religious life among the local population. These documents, compiled from firsthand observations during official trips, consistently underscore the profound impact of Islam on the everyday culture of the faithful in Kazakhstan. The authors highlight a noteworthy discrepancy in the influence of Islam, emphasizing its markedly greater sway on the daily culture of Tatars, Uzbeks, Chechens, and Ingush as compared to Kazakhs. The findings suggest a discernible shift of Islam from mainstream cultural life into a “parallel world,” where pre-Islamic rituals and practices persist in society. Notable among these are fortune-telling based on the Quran and healing rituals performed by “wandering mullahs” employing ushyktau, ushkyru, and the recitation of Quranic surahs. Despite the inherent ideological bias and partiality evident in official documents, the authors argue that these sources remain invaluable for comprehending the impact of Islam on the everyday culture of the Soviet Kazakh population during the 1950s–1960s.